Arab school principals in Israel – between conformity and moral courage. Issue 1 (2nd January 2020) - Reingold, Roni; Baratz, Lea
ABSTRACT: The Arab-Israeli education system is a separate but not autonomous system serving Israel's inhabitants whose first language is Arabic. These include the Muslim and Bedouin majority communities and smaller Christian, Druze and others, whose children attend schools in which the curriculum is determined by a Zionist perspective, taught in Arabic. Thus, in the context of a system established according to the Israeli cultural/national narrative, this study brings to light the voice of ten principals who, through open, in-depth interviews – 'small stories' – reveal their prospective and management of issues-in-conflict to formulate and present their professional identity according to their own sense of self. It presents the conflicts their position confronts vis-à-vis both the formal education authorities and the unique situation their society and culture pose in executing their educational/administrative and moral responsibilities. The findings reveal situations ranging from active acceptance of the institutional dictates of a conformist nature, through passive acceptance, ('conformity') to attempts at promoting autonomous activities within the defined limitations ('moral courage').